Long-term clinical outcomes after a percutaneous coronary intervention with a drug-eluting stent in patients with unprotected left main coronary artery disease excluded from clinical trials. Issue 4 (June 2019) - Oh, Young Soo; Lee, Hyun Jong; Lee, Juneyoung; Choi, Young Jin; Choi, Rak Kyeung; Yu, Cheol Woong; Park, Jinsik; Choi, Jin-Oh; Kim, Je Sang; Kim, Tae-Hoon; Jang, Ho-Jun; Park, Seung Woo; et al.
Abstract : Background: Major randomized clinical trials assessing clinical outcomes in patients who underwent a percutaneous coronary intervention (PCI) for left main coronary artery disease excluded some high-risk subsets. Whether the effectiveness and safety of a percutaneous approach in this group of patients are comparable with those observed in clinical trials is unclear. We aimed to explore the long-term outcomes of contemporary drug-eluting stent (DES)-based revascularization for left main coronary artery disease in patients presenting with one or more clinical or angiographic characteristics who would have precluded inclusion in randomized trials. Patients and methods: Between April 2003 and December 2011, 340 consecutive patients with unprotected left main coronary artery stenosis of at least 50% who underwent successful PCI with DES at Sejong General Hospital (Bucheon, Republic of Korea) were included in this retrospective study. Patients were classified into the exclusion group (group E; n =120) and the inclusion group (group I; n =220) according to the prespecified inclusion and exclusion criteria utilized in clinical trials. Results: During the median follow-up of 86 (52–114) months, major adverse cardiac or cerebrovascular events occurred in 69 (31.4%) patients in group I and 46 (38.3%) patients in group E ( P =0.155). In the propensity score-matched population, group E was not associated with a higher incidence of major adverse cardiac or cerebrovascular events (hazard ratio: 1.42, 95% confidence interval: 0.76–2.65, P =0.758). Definite or probable stent thrombosis occurred in five patients of group I, with no cases in group E. Conclusion: In our real-world registry, about a third of patients who underwent PCI for unprotected left main coronary artery stenosis had one or more high-risk characteristics or comorbid conditions that represent exclusion criteria of previous randomized trials. PCI using DES is feasible in these patients.